Human Abilities / An Information-Processing Approach - Stenberg Robert J (W. H. Freeman And Company, 1985)
This book surveys the major strides made in the past decade toward understanding the full range of human abilities. Preface, Introduction, What is an Information-Processing Approach to Human Abilities?, Genetic Intellectual Ability, Verbal Ability, Reading Ability, Second-Language Ability, Individual Differences in Learning and Memory, Mathematical Ability, Mental Imagery Ability, Deductive Reasoning Ability, Inductive Reasoning Ability, Problem-Solving Ability, Author and Subject Index.